Infectious complications in implant based breast surgery and implications for plastic surgeons - Horch, Raymund E.; Schultz, Gregory; Schubert, Dirk W.; Schmitz, Marweh (GMS German Plastic, Reconstructive and Aesthetic Surgery - Burn and Hand Surgery, 2013)
Implantation of breast prosthesis is still one of the most frequently performed breast reconstructing or contouring procedures. Infectious complications and capsular contracture are inherent problems that may have different causes which are not clearly defined yet in terms of pathophysiology. Recent findings showed bacterial contamination as a major cause of implant failure. Since this has direct implications for the surgical management we report on biofilm development on alloplastic breast prostheses, characteristics and effects after implantation of medical devices in general. This article gives a review of the current literature and discusses possible issues to solve the problem of infection after implantation of breast prosthesis. In conclusion the reinsertion of single-use devices should not be recommended and should be strictly avoided when a device related infection has occured. According to current knowledge contaminated implants should be removed, the infection then be cured and if necessary, a new prosthesis may be implanted after a regeneration period. Alternatively a change in therapy towards autologous tissue reconstruction should be considered if previous attempts with alloplastic prostheses have failed and if radiation therapy has worsened the local tissue situation in the recipient area.